Pemanfaatan Tepung Kulit Singkong Dalam Pembuatan Mi Sagu Instan - Siagian, Ucok Wandi; Pato, Usman; Johan, Vonny Setiaries (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research aim was to find the best formulation for making instant noodle from cassava peel flour and sago starch. This study was conducted using Complete Random Design with three repetitions and six treatments. The treatments for manufacturing instant noodles were  SK0 (sago starch  100%), SK1 (sago starch 95%  and cassava peel flour 5%), SK2 (sago starch 90% and cassava peel flour 10%), SK3 (sago starch 85% and cassava peel flour 15%), SK4 (sago starch 80% and cassava peel flour 20%), and SK5 (sago starch 75% and cassava peel flour 25%). Parameters observed were the moisture content before and after frying, protein content, acid value, intactness and rehydration time. The results show that addition of cassava feel flour significantly affected the moisture content before and after flying, protein content, acid value and intactness, but did not significantly influence the rehydration time of instant noodle. The best treatment was SK5 (sago starch 75% and 25% cassava peel flour) with moisture content before and after frying 9.12 % and 7.12% respectively, protein content 6.14%, acid number 0.03%, intactness 94.93% and  rehydration time 4.23 minutes. Keywords: sago starch, cassava peel flour, instant noodle